Characterization of liposome-encapsulated tylosin, in vitro Cytotoxicity and its antibacterial activitiy against Corynebacterium pseudotuberculosis isolated from goats - Saddiqi, Mohammad Ehsan (2022)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis in goats and it is highly resistant to many conventional antibiotics. Delivery of antibiotics through liposomal encapsulation provides a promising strategy for the effective treatment of resistant bacterial pathogens. The objectives of the study are to characterize, evaluate cytotoxicity and efficacy of liposomal tylosin against C. pseudotuberculosis isolated from goats. Liposomesencapsulated tylosin was produced by the conventional thin-film hydration method. The prepared liposomal dispersions particle size, polydispersity index (PDI), and zeta potential were measured by dynamic light scattering. Cytotoxicity effect of liposome-encapsulated tylosin and free tylosin was evaluated against the normal mouse fibroblast and normal human dermal fibroblast primary cells using MTT assay. The antibacterial activity of free and liposomal tylosin against C. pseudotuberculosis was performed using microbroth dilution and resazurin methods and the antibiofilm activity was evaluated using minimum biofilm inhibitory concentration and minimum biofilm eradication concentration (MBEC) by crystal violet and resazurin-based colourimetric methods. The mean diameter of 171.6 ± 3.22 nm was obtained for liposomal tylosin with 0.236 ± 0.002 and - 4.75 ± 1.6 mV of PDI and zeta potential, respectively. The encapsulation efficiency of liposomal tylosin was 47.7 ± 2.8%. The release behaviour of tylosin from the conventional liposomes is based on initial fast release followed by sustained and slow-released as compared to free tylosin. Cytotoxicity findings revealed higher cell viability (above 70%) for liposomal tylosin and below 70% for free tylosin at a high concentration of 1024 μg/mL. The MIC of conventional, cationic, fusogenic and fuso_cationic tylosin was 32 μg/mL which is much higher than free tylosin with the MIC of 1 μg/mL. In contrast, the MBEC was 1024 μg/mL, 256 μg/mL, 512 μg/mL and 1024 μg/mL for conventional, cationic, fusogenic, and fuso-cationic, respectively, whereas it was 2048 μg/mL for free tylosin. Cationic, fusogenic, and fuso-cationic liposomal tylosin had a mean diameter of 114.8 ± 0.115 nm, 114.4 ± 0.62 nm, and 117.7 ± 1.08 nm, respectively. The cationic liposomal tylosin revealed the average PDI and zeta potential of 0.135 ± 0.014 and 35.3 ± 1.9 mV, respectively, whereas, the mean size of 114.4 ± 0.62 nm, PDI of 0.16 ± 0.019, and zeta potential of -28.6 ± -0.115 mV was recorded for the fusogenic formulation. The fuso-cationic liposomal tylosin showed an average of 117.7 ± 1.08 nm, 0.155 ± 0.01, and 21.83 ± 0.21 mV for size, PDI, and surface charge, respectively. The encapsulation efficiency of cationic, fusogenic, and fuso-cationic liposome-encapsulated tylosin were 34.26 ± 1.15%, 46.63 ± 0.6%, and 41.36 ± 1.2%, respectively. In conclusion, the findings indicate that the liposome as a nanoparticle improved the biocompatibility of tylosin and enhanced the antibacterial activity of tylosin, therefore, it can be considered as a potential strategy to revive the routine antibiotic efficacy against resistant bacteria.